Implementation of Conversion Supplementary Instruments (ISK) Based on Total Quality Management (TQM) at Universitas Brawijaya (Study at the Quality Assurance Center of Universitas Brawijaya) - Athrusy Robiul Hakim; Siti Rochmah; Andy Fefta Wijaya (Wacana Journal of Social and Humanity Studies, 2022)
BAN-PT has recently issued the latest standard, namely IAPS 4.0. IAPS 4.0 has 9 assessment criteria. This assessment replaces the previous criteria, which included 7 criteria (IAPS 3.0). There are fundamental differences that exist between IAPS 3.0 and IAPS 4.0. IAPS's fundamental differences result in unequal accreditation ratings. It is necessary to have a Conversion Supplement Instrument (ISK). The mandatory nature of this national accreditation makes Universitas Brawijaya have to adjust the policies and management of higher education institutions to fulfill the requirements for national accreditation. The success of changing the accreditation status of 80 Study Programs at Universitas Brawijaya has made the researchers interested in doing this research. This research was a case study with a qualitative approach. The result of this research was the implementation of ISK at Universitas Brawijaya was carried out according to the concept of Total Quality Management (TQM). The TQM concept as a PDCA cycle (Plan-Do-Check-Act) had been implemented thoroughly during the implementation of ISK. It started with formulating the ISK policies, procurement of ISK socialization and workshops, and Quality Internal Audits of ISK Assistance Clinics. The implementation of this ISK was very interesting to study because ISK was considered a shortcut for study programs that wanted to change the status of the IAPS 3.0 to IAPS 4.0. Therefore, this research could be a guideline for study programs following ISK. Keywords: accreditation, conversion supplement instruments, total quality management, PDCA Cycle